Advancement of the Subjective Vitality Scale: Examination of alternative measurement models for Japanese and Singaporeans - Kawabata, M.; Yamazaki, F.; Guo, D.; Chatzisarantis, Nikos (Wiley-Blackwell Publishing, Inc., 2016)
The Subjective Vitality Scale (SVS: Ryan & Frederick, 1997) is a 7-item self-report instrument to measure one's level of vitality and has been widely used in psychological studies. However, there have been discrepancies in which version of the SVS (7- or 6-item version) employed between as well as within researchers. Moreover, Item 5 seems not be a good indicator of vitality from a content validity perspective. Therefore, the present study aimed to evaluate the validity and reliability of the SVS for Japanese and Singaporeans rigorously by comparing 3 measurement models (5-, 6-, and 7-item models). To this end, the scale was first translated from English to Japanese and then the Japanese and English versions of the scale were administered to Japanese (n = 268) and Singaporean undergraduate students (n = 289), respectively. The factorial and concurrent validity of the three models were examined independently on each of the samples. Furthermore, the covariance stability of the vitality responses was assessed over a 4-week time period for another independent Japanese sample (n = 140). The findings from this study indicated that from methodological and content validity perspectives, the 5-item model is considered most preferable for both language versions of the SVS.